Solution NMR spectroscopy of single-molecule magnets - Enders, Markus (Reference module in chemistry, molecular sciences and chemical engineering, 2023)
Solution NMR spectroscopy provides access to important structural, electronic, and magnetic properties of single molecule magnets (SMMs), although such data are recorded well above the temperature at which permanent magnetization is maintained. The magnetic anisotropy, an essential requirement for SMMs, is expressed in the NMR spectra and can therefore be determined experimentally by NMR. Delocalization of unpaired electron density onto the ligand framework is another important aspect, which is obtainable from NMR spectroscopy. From the temperature dependence of the NMR chemical shift, the ligand field energy splitting in lanthanide-based SMMs can be obtained and can thus predict the occurrence and quality of SMMs. In SMMs based on transition metals, the splitting energy of the zero field can sometimes be determined. In this overview, equations are presented which are necessary for the interpretation of NMR spectra of paramagnetic compounds, with particular relevance for SMM research. Current solution NMR studies of soluble lanthanide and transition metal SMMs are then discussed.
Online verfügbar: 5. Oktober 2021
Gesehen am 29.11.2022